Outpatient Parenteral Antimicrobial Therapy in Vulnerable Populations— People Who Inject Drugs and the Homeless. Issue 2 (1st February 2019) - Beieler, Alison; Magaret, Amalia; Zhou, Yuan; Schleyer, Anneliese; Wald, Anna; Dhanireddy, Shireesha
Abstract : Outpatient parenteral antimicrobial therapy (OPAT) programs can provide high‐value care but may be challenging in people who inject drugs (PWID) and homeless individuals. We conducted a single‐center, retrospective, cohort study of adults who received OPAT at an urban, public health hospital from January 1, 2015 to April 30, 2016, grouped by PWID and housing status. Outcomes included clinical cure, length of stay, secondary bacteremia, line‐tampering, and readmission. A total of 596 patients (homeless PWID (9%), housed PWID (8%), homeless non‐PWID (8%), and housed non‐PWID (75%), received OPAT. Assuming that patients lost to follow‐up failed therapy, homeless PWID were least likely to achieve cure compared with housed non‐PWID, (odds ratio [OR] = 0.33, 95% CI 0.18‐0.59; P < .001). Housed PWID were also less likely to achieve cure (OR = 0.37, 95% CI 0.20‐0.67; P = .001). Cure rates did not differ in patients not lost to follow‐up. OPAT can be effective in PWID and the homeless, but loss to follow‐up is a significant barrier.